1969
DOI: 10.1002/j.2050-0416.1969.tb03199.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Amino Acids in Bottom Fermentations

Abstract: The net uptake of amino acids in full-scale brewery fermentations with a strain of Saccbaromyces earlsbergensis at 8-9°C. has been followed by analysing amino acids in fermenting wort and beer. The amino acids are usually taken up very incompletely and their uptake follows a certain order, not very different from that observed by British authors using top yeast fermenting at 15" C. The order is not quite constant, however; particularly the uptake of arginine and of ammonia are subject to varia tions. The amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Thus, the amount of free amino nitrogen is important to guarantee a stable fermentation process. For conventional wort (specific gravity of 1.048, 12 P), a FAN level of about 145 mg/L or more is reported to be necessary for a healthy fermentation (39)(40)(41)(42)(43)(44). The results of the current research revealed that all of the teff varieties had higher levels of FAN ( Table 2).…”
Section: Other Malt Quality Attributesmentioning
confidence: 99%
“…Thus, the amount of free amino nitrogen is important to guarantee a stable fermentation process. For conventional wort (specific gravity of 1.048, 12 P), a FAN level of about 145 mg/L or more is reported to be necessary for a healthy fermentation (39)(40)(41)(42)(43)(44). The results of the current research revealed that all of the teff varieties had higher levels of FAN ( Table 2).…”
Section: Other Malt Quality Attributesmentioning
confidence: 99%
“…However, few studies have explored the assimilation of nitrogen compounds when present as a complex mixture of ammonium and amino acids, as found in grape juice. These substrates are generally classified into four groups based on the time and the percentage of removal from the medium during industrial (brewing or wine) fermentations (7,26,27,39,40,43). Nitrogen compounds of the first group are consumed almost totally during the first hours of the fermentation; those of the second group are removed gradually throughout the process; those of the third group are only used after depletion of the compounds of the first group.…”
mentioning
confidence: 99%
“…The Group A amino acids were characterized by fast absorption into the yeast cells (usually complete absorption within 20 h); Group B amino acids were more gradually absorbed into the yeast cell; Group C amino acids were slowly absorbed into the cell after a ‘lag phase’ of around 12 h, while proline, despite being the most abundant amino acid in wort, is only marginally absorbed. Other studies on the absorption of amino acids by brewing yeast in brewery conditions report similar classifications, with minor regrouping of some amino acids (such as reclassifying methionine as a Group A amino acid).…”
Section: Valine Uptakementioning
confidence: 75%
“… also observed that valine uptake was slower in Saccharomyces pastorianus than in Saccharomyces cerevisiae , suggesting that valine could be classified as a Group C amino acid for S . pastorianus fermentations [as suggested by Palmqvist and Äyräpää ].…”
Section: Valine Uptakementioning
confidence: 99%